Galimybių prieiga kaip metapolitinė kategorija: M. Nussbaum teisingumo koncepcijos analizė. - Čekavičius, Laisvūnas (Problems / Problemos, 2022)
Many critics of Martha Nussbaum claim that her account of the capabilities approach is a perfectionist theory that does not provide a unique standpoint to political justice and only complements Rawls' conception of primary goods. The purpose of this article is to show that the capabilities approach differs from primary goods in a sense that the former is orientated towards the ends of a good life, while the latter towards the means. The author argues that the capabilities approach takes an intermediate position between neutrality and perfectionism, maintains a position of relative autonomy, and in turn it can be viewed as a unique metapolitical category, that is to say, a principle of politics capable of accommodating different political views.